An SSR-based molecular genetic map of cassava - Okogbenin, Emmanuel; Marín, J.A.; Fregene, Martin A. (Springer, 2006)
Microsatellites or simple sequence repeats (SSR) are the markers of choice for molecular genetic mapping and marker-assisted selection in many crop species. A microsatellite-based linkage map of cassava was drawn using SSR markers and a F2 population consisting of 268 individuals. The F2 population was derived from selfing the genotype K150, an early yielding genotype from an F1 progeny from a cross between two non-inbred elite cassava varieties, TMS 30572 and CM 2177-2 from IITA and CIAT respectively. A set of 472 SSR markers, previously developed from cassava genomic and cDNA libraries, were screened for polymorphism in K150 and its parents TMS 30572 and CM 2177-2. One hundred and twenty two polymorphic SSR markers were identified and utilized for linkage analysis. The map has 100 markers spanning 1236.7 cM, distributed on 22 linkage groups with an average marker distance of 17.92 cM. Marker density across the genome was uniform. This is the first SSR based linkage map of cassava and represents an important step towards quantitative trait loci mapping and genetic analysis of complex traits in M. esculenta species in national research program and other institutes with minimal laboratory facilities. SSR markers reduce the time and cost of mapping quantitative trait loci (QTL) controlling traits of agronomic interest, and are of potential use for marker-assisted selection (MAS).